GEOLOGI BAWAH PERMUKAAN DESA DAMBALO KECAMATAN TOMILITO KABUPATEN GORONTALO UTARA - Male, Cindi Claudia; Zainuri, Ahmad; Akase, Noviar (Sustainability (STPP) Theory, Practice and Policy, 2024)
Dambalo Village, Tomilito District, North Gorontalo Regency, Gorontalo Province, is the designated research area listed in the administrative records. The main objectives of this research are to determine the surface and subsurface geology, understand the geological conditions of the research area, and analyze the cross-section of subsurface geological layers. The study employs the Schlumberger configuration geoelectric method to examine the subsurface geological cross-section. The researchers used a combination of geological surveys and subsurface data surveys, collecting data on surface geological features, outcrop observations, and resistivity measurements. The research area features a single landform unit, the denudational plain, and its stratigraphy includes a lithostratigraphic unit, Volcanic Breccia. The study area comprises four rock layers: the first layer is topsoil (passive clay), the second layer is sand, the third layer is breccia, and the fourth layer is sand. These conclusions are supported by geological and geoelectric data, demonstrating the effectiveness of integrating surface and subsurface surveys to provide a comprehensive understanding of the geological structure.